'Emptying Forests?' Conservation Implications of Past Human–Primate Interactions. (April 2021) - Amano, Noel; Wang, Yiming V.; Boivin, Nicole; Roberts, Patrick
Abstract : Non-human primates are among the most vulnerable tropical animals to extinction and ~50% of primate species are endangered. Human hunting is considered a major cause of increasingly 'empty forests', yet archaeological data remains under-utilised in testing this assertion over the longer-term. Zooarchaeological datasets allow investigation of human exploitation of primates and the reconstruction of extinction, extirpation, and translocation processes. We evaluate the application and limitations of data from zooarchaeological studies spanning the past 45 000 years in South and Southeast Asia in guiding primate conservation efforts. We highlight that environmental change was the primary threat to many South and Southeast Asian non-human primate populations during much of the Holocene, foreshadowing human-induced land-use and environmental change as major threats of the 21st century. Highlights: South and Southeast Asia are hotspots for non-human primate biodiversity but also home to critically endangered and vulnerable species. Zooarchaeology can help guide primate conservation efforts in South and Southeast Asia but has been under-utilised. Conservation research often emphasises human hunting as the major cause of primate extinction; however, zooarchaeological and palaeoenvironmental data suggests habitat change has also played a major role. Zooarchaeology can provide species-specific suggestions for endangered primate taxa, such as orangutan.